FAKTOR PENYEBAB PARTISIPASI ANGKATAN KERJA WANITA PADA SEKTOR INDUSTRI KAYU LAPIS (STUDI KASUS PT. SSTC) KECAMATAN BANJARMASIN BARAT KOTA BANJARMASIN - Mery Mentari Noor; Ellyn Normelani; Karunia Puji Hastuti (JPG (Jurnal Pendidikan Geografi), 2016)
The title of this research is “The Factors Causing of Female Labor Force Participation In Plywood Industry Sector (Case Study PT. SSTC Surya Satrya Timur Croporation) at the Village of Kuin Cerucuk District of West Banjarmasin City. The purpose of this research was to determine the factors that led to high labor force participation of women in the PT. SSTC at the Village of Kuin Cerucuk  District of West Banjarmasin City.  The method which use in this research is a descriptive quantitative method. Population in this research were all female labor force PT. SSTC at  Village of Kuin Cerucuk District of West Banjarmasin City amounting to 790 people. The determination of the number of samples in this research  used Krejcie and Morgan table. The numbers of sample research used Krejcie and Morgan table with 790 population known as 259 samples. This research used a primary and a secondary data. Primary data obtained through observation in the field and spread the questionnaire, secondary data obtained from study of library, study of document, and from internet. The research used a percentage (%) analysis techniques. The research results shows thats the factors causing female labor force participation in PT. SSTC at the Village of Kuin Cerucuk District of West Banjarmasin City are internal factors  (the willingness of the self), which the willingness to work. Keywords: Causing Factor,Participation, The Female Labor Force, PT. SSTC Banjarmasin